A computable general equilibrium model for the examination of worldwide agricultural liberalization policies: Model structure and preliminary results - Hans Fehr; Wolfgang Wiegard (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1995)
This paper presents the technical background for our computable general equilibrium (CGE) analysis of different worldwide liberalization scenarios in agricultural markets. The main features of the examined agricultural protection policies are explained and descriptions of the applied economic model and the construction of a disaggregated multi-country dataset are provided, as well as documentation of calibration for a benchmark year. Finally we present some preliminary results of simulated liberalization schemes. The explanation of these results is not included. This will be done in more specific papers.
Keywords: 330; Handelsliberalisierung; Allgemeines Gleichgewicht; Wirtschaftsmodell; Theorie; Welt; Außenwirtschaftspolitik